Lactotransferrin gene functional polymorphisms do not influence susceptibility to human immunodeficiency virus-1 mother-to-child transmission in different ethnic groups. - Zupin, Luisa; Polesello, Vania; Coelho, Antônio Victor Campos; Boniotto, Michele; Arraes, Luiz Claudio; Segat, Ludovica; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2015)
Lactotransferrin, also known as lactoferrin, is an iron binding glycoprotein that displays antiviral activity against many different infectious agents, including human immunodeficiency virus (HIV)-1. Lactotransferrin is present in the breast milk and in the female genitourinary mucosa and it has been hypothesised as a possible candidate to prevent mother-to-child HIV-1 transmission. To verify if two functional polymorphisms, Thr29Ala and Arg47Lys, in the lactotransferrin encoding gene (LTF) could affect HIV-1 infection and vertical transmission, a preliminary association study was performed in 238 HIV-1 positive and 99 HIV-1 negative children from Brazil, Italy, Africa and India. No statistically significant association for the Thr29Ala and Arg47Lys LTF polymorphisms and HIV-1 susceptibility in the studied populations was found. Additionally LTF polymorphisms frequencies were compared between the four different ethnic groups.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Brazil; Child; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; HIV-1; Humans; India; Infant, Newborn; Infectious Disease Transmission, Vertical; Italy; Lactoferrin; Male; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction; Retrospective Studies; Zimbabwe